Topographic distribution pattern of Posthodiplostomum sp. metacerccariae on body surface of cyprid fishes of river Ganga - Baitha, Raju; Manna, Sanjib Kumar; Suresh, Vettath Raghvan; Paniprasad, K.; Naskar, Malay (Journal of the Inland Fisheries Society of India, 2019)
The clinical condition â€˜blackspotâ€™, caused by larval stage (metacercariae) of digenetic trematodes, is observed in fishes of inland freshwater. Topographic distribution of Posthodiplostomum sp. metacercariae on body surface of cyprinid fish species, Pethia conchonius and Catla catla were investigated. Quarterly samplings were conducted in lower stretch of river Ganga from Farakka to Balagarh and sectoral abundance of metacercariae of the trematode parasite within and between the fish species were compared. The Sector or body region 1 (S1: head, gill, operculum, eyes and buccal cavity) and Sector 2 (S2: body trunk below imaginary line) of C. catla and P. conchonius were found to be the most infected parts in the respective host. But Sector 4 (S4: fins excluding fin base) did not harbour any parasite in both the host species. Foraging behaviour and habitat preference might be the reasons for differential distribution pattern of the fish parasite stage, but absence of infection in the fins could be related to comparative difficulty in attachment and penetration of fins by the cercariae. Key wordsÂ Â Posthodiplostomum sp., Pethia conchonius, Catla catla, metacercaria, river Ganga